A revision of the genus Xenochilicola (Hymenoptera: Apoidea, Colletidae), with the description of a new species - Genaro, Julio A.; Packer, Laurence (Zootaxa, 2005)
The bee genus Xenochilicola (Colletidae: Xeromelissinae) is revised. Three species are recognized, with one described as new: X. haroldotoroi, only known from males. Xenochilicola fulva is proposed as a new junior synonym of X. diminuta. A key to species is provided.